PENGELOLAAN BANK SAMPAH DI DESA TADANG PALIE KECAMATAN CEMPA KABUPATEN PINRANG SEBAGAI UPAYA PENGURANGAN SAMPAH DAN PENINGKATAN EKONOMI MASYARAKAT - Herlina, Herlina; Kasman, Marissa; Alsa, Nur Amalia; Rahmadani, Suci; Mutmainna, Mutmainna; Bazyrah.S, Sri Tengku; Wijaksana, Widya (Mediasi: Jurnal Pengabdian Masyarakat, 2026)
Waste management is one of the main environmental problems in rural areas, including Tadang Palie Village, Cempa District, Pinrang Regency. The community still faces challenges in sorting and processing household waste, which causes environmental pollution and health risks. This community service program aims to strengthen the implementation of the waste bank system as an effort to reduce waste volume and improve the local community’s economy. The methods used include socialization, training on waste sorting, establishment of waste bank management, and assistance in waste collection and recycling activities. The results show an increase in community awareness and participation in waste management. The waste bank program helps residents save through waste deposits and supports environmental cleanliness. This activity contributes to sustainable village development and encourages community-based waste management practices.